2022
DOI: 10.1002/eem2.12340
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Proton Migration Kinetics by Ni2+ Regulating Enables Improved Aqueous Zn‐MnO2 Batteries

Abstract: The energy storage behaviors of MnO2 for aqueous Zn‐MnO2 batteries mainly depend on the Zn2+/H+ intercalation but are limited by poor ion/electron migration dynamics and stability. Herein, a strategy is proposed that promoting proton migration kinetics ameliorates H+ storage activity by introducing Ni2+ into γ‐MnO2 (Ni‐MnO2). Ni2+ can lower the diffusion barrier of H+ and selectively induce the ion intercalation, thereby alleviating the electrostatic interaction with the lattice. Moreover, Ni2+ enables the adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…The b values of 0.98/0.99 (P 3 /P 3 ′) suggest that the reaction between −0.45 and −0.3 V is surface controlled. [47] In this context, the superior reaction kinetics likely comes from fast desolvation and good electron/ion conductivity. R ct at different temperatures are used to calculate the apparent activation energy (E a ) for the desolvation process on the electrode/electrolyte interface (Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The b values of 0.98/0.99 (P 3 /P 3 ′) suggest that the reaction between −0.45 and −0.3 V is surface controlled. [47] In this context, the superior reaction kinetics likely comes from fast desolvation and good electron/ion conductivity. R ct at different temperatures are used to calculate the apparent activation energy (E a ) for the desolvation process on the electrode/electrolyte interface (Figure S14, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that the specific capacity and rate capability of NMO/rGO are comparable to or better than many other reported cathode materials. [ 10–13,18,33,34 ]…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] Ji et al reported that Ni-γ-MnO 2 exhibited excellent rate performance and ultralong cycling stability (100% capacity retention after 11 000 cycles at 3.0 A g À1 ), because Ni 2þ doping can reduce the diffusion barrier of H þ , alleviate the electrostatic interaction with the lattice, and improve the electronic conductivity of materials. [11] Zhang et al reported that Ni-doped Mn 2 O 3 (NM) showed a high specific capacity of 252 mAh g À1 (0.1 A g À1 ), which is three times higher than that of pure Mn 2 O 3 (72 mAh g À1 ). It is found that Ni 2þ doping can improve electrical conductivity, the reaction kinetics, and the electrochemical properties of NM.…”
Section: Introductionmentioning
confidence: 99%
“…By changing the electronic state structure of t 2 g 3 egfn1 with high spin of Mn 3+ and substituting transition metal elements for Mn 3+ , the structural stability of MnO x cathode material is improved to suppress the J-T effect, so as to improve its cycle stability, which has been deeply studied in the application of lithium/sodium ion batteries (Li et al, 2009;Xiao et al, 2018). Defect engineering (such as vacancy and doping) can improve the structural stability of MnO x , inhibit Mn 3+ disproportionation caused by J-T effect, and improve the cycle stability of MnO x zinc storage process (H Zheng et al, 2022;Ji et al, 2022). At present, part of the work has carried out defect engineering research on manganese-based cathode materials for aqueous zinc ion batteries.…”
Section: Bulk-phase Regulationmentioning
confidence: 99%